Pelaksanaan Pemenuhan Program Badan Penyelenggara Jaminan Sosial Ketenagakerjaan Terhadap Pekerja (Studi Pada Bali Safari and Marine Park) - I Dewa Gede Dwipayana Putra; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Jurnal Preferensi Hukum, 2022)
The role of workers is very important for the development of the national economy, therefore the higher the challenges and risks that will be faced by the workers so that all need to be given protection, maintenance, and improvement of welfare for workers who become basic protectors with the aim of meeting the needs of life for workers. The purposes of this study are to analyze the implementation of the agency's program for administering employment social security for workers in Bali Safari and Marine Park as well as the obstacles and efforts made by Bali Safari and Marine Park workers in implementing the program of the agency for administering labor social security. This research method is an empirical research with a case and conceptual approach. The data collection technique was carried out by observation techniques in the form of interviews. The data sources used are primary and secondary legal sources. After the data is collected, it is then analyzed qualitatively. The results of the study revealed that the protection of workers was not appropriate in fulfilling the Organization for Employment Social Security at the Bali Safari and Marine Park company as stipulated in Law no. 40 of 2004 concerning Social Security, because not all workers are registered in the program of the Social Security Administering Body. The obstacles faced by workers are related to the working period which is only 1 to 3 months, especially for casual daily workers, and extensions will not necessarily be carried out, because there are already permanent and contract workers in their respective fields.